Components of effective safety and health management system towards the awareness of Occupational Safety and Health Administration (OSHA) at government owned company Kuala Lumpur / Noorlaila Hj Yunus and Nur 'Aliya Hj Abdullah Tahmidi - Yunus, Noorlaila; Abdullah Tahmidi, Nur 'Aliya (Universiti Teknologi MARA, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2018)
Every organization should put safety and health of employees at the top of priority. A safety and health management system or safety program can help the employees to improve job performance, boost employee's motivation and satisfaction. The most important is employers and employees will feel secure and safe at the workplace. Occupational Safety and Health Administration (OSHA) in an organization could help to prevent any possible illnesses, injuries and accidents happen in working environment. Several studies have been conducted that clarified some of the components of effective safety and health management systems towards the awareness of OSHA. The focus of this study is to identify the most influential components of effective safety and health management systems towards the awareness of OSHA and also to examine the relationship between the components of effective safety and health management systems towards the awareness of OSHA. Thus, the researcher chooses correlational research design in order to achieve the objectives of the study. In this study, 250 employees who are working in GOC, Kuala Lumpur have been involved in a survey.